Assessment of the radiological safety of Pridneprovskiy chemical plant's tailings - V. K. Kyrychenko; V. O. Kashparov (Ядерна фізика та енергетика)
Analysis of the influence of the tailings of uranium production from Pridneprovsk chemical plant of agricultural products with heavy natural radionuclides (210Pb, 210Ро, 226Ra, 232Th, 238U) in adjacent areas of agricultural assignment was performed. Additional radiation doze to the population, living in the zone of influence of the tailings was determined.